2018
DOI: 10.4013/nbc.2018.133.08
|View full text |Cite
|
Sign up to set email alerts
|

Update of the distribution of Lonchorhina aurita (Chiroptera), a vulnerable cave-dwelling bat in Brazil

Abstract: Lonchorhina aurita is an insectivorous cave-dwelling bat, which roosts primarily in caves, and has been reported from three (Cave Pedra Branca, Cave Janela, and Cave Raposa) of the 94 natural caves registered in Sergipe by the National Register of Speleological Information/National Center for Cave Research and Conservation.The subfamily Lonchorhininae encompasses bats that can be distinguished from other phyllostomids by the presence of an extremely well-developed nasal leaf, which is as long as the ears. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…An alternative possibility of direct transmission of T. dionisii among bats in this region should be considered due to their habit of aggregating into colonies [ 16 ]. The isolate M1011 was isolated from the insectivorous bat L. aurita , described as having cave-dwelling and colony-forming habits [ 46 ]. In a captive study, Thomas et al [ 47 ] demonstrated that bats can be infected by different species of trypanosomes orally via the ingestion of triatomines as well as through contamination when exposed to the feces and urine of these insects or through bites.…”
Section: Discussionmentioning
confidence: 99%
“…An alternative possibility of direct transmission of T. dionisii among bats in this region should be considered due to their habit of aggregating into colonies [ 16 ]. The isolate M1011 was isolated from the insectivorous bat L. aurita , described as having cave-dwelling and colony-forming habits [ 46 ]. In a captive study, Thomas et al [ 47 ] demonstrated that bats can be infected by different species of trypanosomes orally via the ingestion of triatomines as well as through contamination when exposed to the feces and urine of these insects or through bites.…”
Section: Discussionmentioning
confidence: 99%